Gender Differences in Denial-Acceptance Duration Based on Kübler-Ross Cycle After HIV Diagnosis - Niniek Budiarti Burhan; Muhammad Reza Febriliant (Fakultas Kedokteran Universitas Brawijaya, 2021)
Patients who have been diagnosed with HIV often suffer from sadness and grief that, in turn, affect the adherence to HIV treatment. This study aimed to examine gender differences in the denial-acceptance duration based on the Kübler-Ross cycle in patients after diagnosed with HIV. A cross-sectional survey was conducted on 63 adult HIV patients aged 19-60 years who received routine treatment at the HIV/VCT outpatient department of Saiful Anwar General Hospital Malang. Subjects were interviewed using the Acceptance of Disease and Impairments Questionnaire (ADIQ). Gender differences in denial-acceptance duration after diagnosed with HIV were analyzed using the unpaired T-test. Results were statistically significant if p value <0.05. The median duration of denial-acceptance in male subjects was 16 weeks with the shortest duration of 1 week and the longest duration of 144 weeks, while the median duration of female subjects was 12 weeks with the shortest duration of 1 week and the longest duration of 240 weeks. There are no gender differences in the denial-acceptance duration (p value = 0.629). In conclusion, there are no gender differences in denial-acceptance duration based on the Kübler-Ross cycle after diagnosed with HIV.